The Effectiveness of A Training Program Using Mini-Spaces in Improving Collective Possession among Soccer Players - Belmahi, Salim (Journal of Ecohumanism, 2025)
The study aims to identify the effectiveness of a training program in small spaces and its role in improving collective possession among football players. For this purpose, we used the experimental method on a sample consisting of three teams, each team comprising 18 players - classified as Cubs - from the original research community, divided into three sections. (One team represents the experimental sample, one team represents the control sample (1), and one team represents the control sample (2)), After collecting the results and processing them statistically, the researchers concluded that the training program applied to the experimental sample in the mini-spaces improves the method of collective possession as a function of time and passing, which recommended that football teams and academies should program special training sessions and units for the mini-spaces in the younger groups. For its role in improving the technique of ball possession, which is often the reason for winning matches.